DEVELOPMENT, GOALS, OBJECTIVES AND ESSENCE OF COMPLEX ECONOMIC ANALYSIS OF ACTIVITY OF ENTERPRISES - A. Dvoryankina; T. Rogulenko (Вестник университета, 2017)
In the article, the key stages of development of the complex economic analysis of economic activity are considered. The goals, tasks and essence of complex economic analysis are determined. The cases in which there is a need for comprehensive economic analysis are considered. The sequence of stages of the complex analysis procedure listed. The classification of information sources for economic analysis of economic activity is given. The main components of the integrated economic analysis of industrial enterprises singled out. Distinctive features of the complex economic analysis at the enterprises of trading networks are marked.